2017
DOI: 10.1149/2.0211711jss
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Deep-Level Trap Distributions in AlGaN/GaN HEMTs and Its Influence on Transient Analysis of Drain Current

Abstract: AlGaN/GaN high electron mobility transistors for high efficiency power switching applications are susceptible to charge trapping by deep-levels in the GaN buffer resulting in current collapse during gate and drain voltage swings. Although drain-current transient based methodologies have been used consistently to extract trap parameters, the factors affecting the non-exponential nature of the transient are still not well understood. No effort at accurately replicating multiple deep-levels in the GaN buffer to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The boundary conditions at the Ga 2 O 3 surface, where the reaction rate is assumed to be large (10 6 s −1 , based on previous results for semiconductor surface-dominated reactions), [30][31][32] where K S is the surface outgas rate of 2 H. Finally, the change in trapped deuterium concentration as a function of time, (which increases when mobile atoms are captured and decreased when these are released) is given by:…”
Section: Models For Diffusion In the Cases Of Implant Damage Or Plasm...mentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions at the Ga 2 O 3 surface, where the reaction rate is assumed to be large (10 6 s −1 , based on previous results for semiconductor surface-dominated reactions), [30][31][32] where K S is the surface outgas rate of 2 H. Finally, the change in trapped deuterium concentration as a function of time, (which increases when mobile atoms are captured and decreased when these are released) is given by:…”
Section: Models For Diffusion In the Cases Of Implant Damage Or Plasm...mentioning
confidence: 99%
“…The dominant mechanisms for the outdiffusion kinetics are extracted from simulations using the Florida Object Oriented Process Simulator (FLOOPS) simulator. [29][30][31][32] We have previously reported that only 12% of the initial dose remains in 2 H implanted Ga 2 O 3 after annealing at 650 • C and that the diffusivity of plasma introduced 2 H at 270 • C is of order 6.4 × 10 −13 cm −2 . 21,28 However, we did not investigate the mechanisms in detail.…”
mentioning
confidence: 99%
“…All electronic equipment has standard capacitors, which store an electrical charge when a voltage is supplied to them. They are trapped by deep energy level traps positioned in the buffer and the substrate if the pulse duration is larger than the constant of capture time and less than the constant of emission time [27]. These electrons caught by the traps do not contribute to the current flowing through the channel [28].…”
Section: Capacites Analysismentioning
confidence: 99%
“…Ideally, the trapping phenomena originate from defects with discrete energy levels, and the DCT profile behaves as a pure exponential decay function (e −t/τ ). However, it has been shown that this rarely happens in real HEMTs, where more complex defect distributions and/or surface states can play a significant role [8], [9], [10], [11], [12]: transients are strongly stretched (e −(t/τ ) β ) due to the fact that defects are distributed in energy and/or in space.…”
Section: Introductionmentioning
confidence: 99%